The Impact of Modern Technologies on Life in a Pandemic Situation - Budayová, Zuzana; Pavliková, Martina; Samed Al-Adwan, Ahmad; Klasnja, Kristina (Journal of Education Culture and Society, 2022)
Aim: ​ The Covid-19 pandemic situation has affected all sectors of our society that have been in direct or indirect contact with humans. The virtual world, which did not concern many people until the onset of the pandemic, began to be a major part of the solutions to everyday situations in life. Modern technologies thus began to play a major role in solving problem situations, but also in the ordinary contact of people with the school, with medical facilities, with work, in communication with other close relatives. Concept: The use of modern technological equipment and their connection to the pandemic situation began to be of interest in the professional and research investigation of scientists working in various areas of life. In addition to the use of modern technological equipment, other more abstract ideas have begun to be explored, reflecting and commenting on, comparing the advantages and disadvantages of using equipment on the basis of age, ability and industry. Scientific studies are thus carried out from the point of view of sociology, gender studies, psychology, psychiatry, medicine, social work, but also other inhumane scientific branches. Method: This study addresses the advantages and disadvantages of using modern technology and points to a number of studies that positively or negatively affect a person’s personality through the virtual world. The authors of this study worked with specific texts, using textual analysis, analytical and synthetic methods, and pointed out important studies that draw attention to the connection between the social situation and the use of modern technologies. Results: ​​ The study confirms that the pandemic situation requires constant access to virtual reality through modern technological devices that allow all people in society to contact each other, regardless of age, gender, job classification, or position, role. At the same time, it is very important how we will incorporate modern technologies into our lives and what impact modern devices will have on survival and on the real world. Conclusion: The scientific articles and contributions offered in this study point to the use of technological devices, their advantages and disadvantages for the development of human personality. It is understandable that the virtual world can interfere with our personal and family life, while it is necessary to realize its basic functions, which it offers us for our benefit.